Jawabanmu

Jawaban paling cerdas!
2014-06-10T14:43:52+07:00
F(x) = px³ + qx² - 49x + 30 , f(2/3) = 0 dan f(-5) = 0
p(2/3)³ + q(2/3)² - 49(2/3) + 30 = 0
8p/27 + 4q/9 - 98/3 + 30 = 0  kalikan dengan 27 didapat
8p + 12g - 882 + 810 = 0
8p + 12q = 72 .....................(1)

p(-5)³ + q(-5)² - 49(-5) + 30 = 0
-125p + 25q + 245 + 30 = 0
-125p + 25q = -  275  bagi dengan - 25
 5p - q = 11 kalikan dengan 12
60p - 12q = 132  ....................(2)
8p  + 12q = 72 +
68p = 204
p = 204/68 = 51/17 = 3
8p + 12q = 72 ⇔ 24 + 12q = 72 ⇔ 12q = 72-24 ⇔ 12q = 48 berarti q = 4
Jadi p.q = 3(4) = 12

1 5 1